Pengembangan Media Pembelajaran Game Education Berbasis Gamifikasi Pada Mata Pelajaran Pendidikan Pancasila Kelas IV Sekolah Dasar - Ola Kurnia Putri; Atri Waldi (Universitas Negeri Padang, 2025)
This research is motivated by the minimal use of learning media that implements technological elements in schools. Considering the characteristics of class IV students who like games, this research aims to develop gamification-based game education learning media for class IV elementary schools. The type of research used was development research (R&D) with the ADDIE development model, namely analysis, design, development, implementation, and evaluation. Data collection was carried out through validity sheets and media practicality questionnaires. The research results showed that the validity test value for the material aspect was 96.5%, the media aspect was 93.7%, and the language aspect was 95.6% in the very valid category. Based on the results of the teacher and student response questionnaire at the trial school, a percentage of 95.8% was obtained for teacher responses and 92.9% for student responses in the very practical category. Furthermore, the results of the teacher response questionnaire and student responses at the distribution schools showed percentage results of 100% and 92.7% in the very practical category. Thus, it can be concluded that the gamification-based game education learning media in class IV elementary school pancasila learning subjects has been declared valid and practical for use.